7n+6-6n=-1

Simple and best practice solution for 7n+6-6n=-1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7n+6-6n=-1 equation:


Simplifying
7n + 6 + -6n = -1

Reorder the terms:
6 + 7n + -6n = -1

Combine like terms: 7n + -6n = 1n
6 + 1n = -1

Solving
6 + 1n = -1

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '-6' to each side of the equation.
6 + -6 + 1n = -1 + -6

Combine like terms: 6 + -6 = 0
0 + 1n = -1 + -6
1n = -1 + -6

Combine like terms: -1 + -6 = -7
1n = -7

Divide each side by '1'.
n = -7

Simplifying
n = -7

See similar equations:

| w^25=w | | n+n+1+n+2=-24 | | 6=8k-(10k+3) | | 3(3n+2)=9(4n+5)+8 | | 6x+y=98 | | -40-2b=-2+2(1-5b) | | 56=4x | | w^25= | | A(x-2)(x-3)= | | 2+m=-10 | | 6x+9=-108-7x | | -8q-3(q+4)=q+7 | | 6x+9=-1008-7x | | x-(-3)=-1 | | -4y-13=9y+13 | | -3+9x=3(x+6) | | 18b=-234 | | 2x+30=12x | | 3c+c=48 | | 4q+2(-8+3q)=3 | | 8x-73=3x-13 | | 3x-7=7x-9 | | -11n=99 | | 2-5v-6v=2 | | 2-5v-6v=23 | | 12-7x=144-35x | | 42=-3(4n-2) | | -p-8p=3-6p | | -32=-2v | | -2a+5=5 | | 6(2x-9)=-102 | | -4n=-n-6 |

Equations solver categories